Breast cancer spinal metastases: Prognostic factors affecting survival after surgery. A retrospective study. (August 2020) - Terzi, Silvia; Trentin, Federica; Carretta, Elisa; Pipola, Valerio; Ghermandi, Riccardo; Barbanti Bròdano, Giovanni; Ferrari, Cristina; Griffoni, Cristiana; Gasbarrini, Alessandro
Highlights: Retrospective cohort study of patients affected by breast cancer spinal metastases surgically treated. Concurrent bone metastases and preoperative neurological impairment are independent prognostic factors. The study of prognostic factors is relevant to evaluate the most appropriate surgical treatment. Abstract: Breast cancer spinal metastases (BCSM) are common and require proper treatment that leads to an improvement of the quality of life and contributes to the quod vitam prognosis. Surgical treatment is often required for intractable pain, spinal cord compression or spinal instability. The aim of this retrospective study is to identify which prognostic factors could affect postoperative overall survival in patients affected by BCSM. We report a retrospective cohort study of patients with BCSM, surgically treated from September 2009 to May 2018. Demographic and clinical data were collected. Kaplan-Meier method was used to estimate overall survival, and the log-rank test was used to compare survival curves. A total of 77 patients were studied. The median age at the time of surgery was 54 years. The median follow-up was 49 months. The 3-year and 5-year overall survival rates were 61% (95%CI: 47.5–72.1) and 43.3% (95%CI: 28.8–57.1). Metastatic bone disease (p = 0.0196), preoperative neurological impairment (p = 0.0029), Karnofsky status <70 (p = 0.0241) reduce survival. With multivariate analysis, the effect of Karnofsky score loses statistical significance. The presence of concurrent bone metastases and a preoperative neurological deficit are independent prognostic factors. Therapeutic choices are based on a multidisciplinary assessment that takes into consideration several factors, including an accurate study of prognostic factors.